Historical Memory and the Holocaust: Perception of the Problem - Vitkus, Hektoras (Genocidas ir rezistencija, 2025)
The relationship of historical memory to the problem of the Holocaust has affected the strategies of Lithuanian historical consciousness. Interactionalist and functionalist conceptions may be applied to reveal this aspect of their relationship. First, emphasis is placed on the possibilities for the conformity of historical memory and the problem of the Holocaust; second, on the modalities of these possibilities which affect how historical memory is formed: that is, the conflicting individual, group or collective interests, their cooperation, dominance and antagonisms. Both concepts might reveal the characteristics of the Holocaust in individual, collective and public forms of historical memory which are less well-known in Lithuania.The most important characteristics of the relationship of the Holocaust and historical memory become clear in the interaction between the individual and public historical memory. It may be approached by both quantitative and qualitative methodologies. These methods are the way to better understand and systemize the consistent patterns of cultural policy of historical memory.The relationship of the historical memory and the Holocaust, both in Lithuania and in other societies, may be defined by three principles of historicism: recognizing the differences of various epochs, searching for the context, and insight into the process of historical development. These perspectives disclose the effects of the historical consciousness which distort historical memory of the Holocaust: references to tradition, nostalgia, the belief in progress. These phenomena manifest themselves in the society's "crises of the historical memory" caused by the problem of the Holocaust. In these "crises" we see the strategies of historicizing negative experience that are common to the individual, group or collective historical memory: the stress on the anonymous, categorization, normalization, moralization, emphasizing aesthetics and specialization.These aspects can help us predict the scenarios of possible changes in the historical memory of the Holocaust.
Keywords: Holocaust; historical memory; society